KONDISI FISIK ATLET LEMPAR CAKRAM (DISCUS THROW) PUSAT LATIHAN NASIOANAL B DI SURABAYA - Wulandari, Fifit Yeti (JSES : Journal of Sport and Exercise Science, 2021)
Discus throwing really requires good physical condition, especially in discus throwing, it requires flexibility and explosive power and other physical components. Not only explosive power, other physical conditions play a very significant role in discus throwing, including strength, speed, endurance, flexibility, coordination and balance. This research is a quantitative research with an ex-post facto descriptive approach. In this study, the focus was on the physical condition of the PLATNAS B Discus Throwing athletic athletes. The subjects of this study were 4 PLATNAS B Discus Throwing athletes consisting of 3 men and 1 woman. Based on the results of the research, it was concluded that the physical component of the speed of the PLATNAS B Discus Throwing athletes obtained "good" results for 3 athletes (80%) and 1 athlete (20%) "enough". So that it can be concluded that the speed is in the "good" category. The explosive power component of the disc-throwing athlete's limbs PLATNAS B obtained "very good" results 2 athletes (50%) "good" 1 athlete (40%), and "enough" 1 athlete (10%). So it can be concluded that the explosive power of the leg muscles is in the "good" category. The component of the arm muscle strength of the PLATNAS B Discus Throwing athletes obtained "good" results for 3 athletes (70%) and "enough" for 1 athlete (30%). So it can be concluded that the arm muscle strength is in the "good" category. The component of abdominal muscle strength for disc throwing athletes PLATNAS B obtained "good" results for 3 athletes (60%) and "enough" for 1 athlete (40%). So it can be concluded that the strength of the abdominal muscles is in the "enough" category. The component of the reaction speed of the PLATNAS B Discus Throwing athletes obtained "good" results for 3 athletes (60%) and "enough" for 1 athlete (40%). So it can be concluded that the reaction speed is in the "enough" category.